Awareness of the Communist Government in Czechoslovakia about Emigrants and Exiles in Australia in 1950s and 1960s - Buresova, Jana (Historica Olomucensia, 2014)
A relatively large collection of written sources of the Czechoslovak provenience, its government and institutes, are materials coming from activities of the Czechoslovak Foreign Institute, the Consulate General in Sydney and the emigrant Czechoslovak Club in Sydney. Representatives of these institutes officially communicated together, informed each other and cooperated because of their mutual goals. Czechoslovak Communist government also received information about exiles from its secret policy, which utilized sources of secret collaborators from ranks of civil inhabitants as well.Czechoslovak Communist government attempted to have an overview of the exile in Australia and strived for a successful influence on compatriots, exiles included. The Czechoslovak Club in Sydney, as the only loyal organisation in Australia, struggled for the propagation of the Communist regime in Czechoslovakia. Information about exiles and their cultural and social activities in Australia gradually and often sketchily came to leading forces in Czechoslovakia and were acquired through intermediated ways and sources.
Keywords: exile; Australia; Czechoslovakia; the 20th century